Handelbare Verschuldungsrechte zur Sicherung fiskalischer Stabilität in der Währungsunion? - Renate Ohr; André Schmidt (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2006)
The Stability and Growth Pact is one of the constituent pillars of the European Monetary Union. Though, meanwhile it is obvious that it will not be able to limit fiscal deficits of the member states. For this reason in this paper Coase's thinking in institutional alternatives is applied to find a better way to increase the incentives for more fiscal stability. We present and discuss tradable deficit permits comprising market-orientated incentives for fiscal stability. It is shown that tradable deficit permits are superior from a politico-economical view as well as with regard to allocative efficiency.
Keywords: E5; E6; H6; 330; stability and growth pact; tradable deficit permits; monetary union